Reinterpretasi Muhammad Shahrur dalam Konsep: "Lā Ikrāha fī al-Dīn" - Hanif, Imam Padhlurrahman (Asian Journal of Islamic Studies and Da'wah, 2024)
Muhammad Shahrur is one of the contemporary mufasirs who uses a linguistic approach in his interpretations. Among them is his interpretation of the concept that there is no compulsion in Islam (Lā Ikrāha Fī al-Dīn). The concept discusses the meaning of freedom, starting from the misunderstanding of some people in interpreting freedom, as well as their confusion in carrying out commands or prohibitions, especially in religion, whether they live it out of obedience or compulsion. For this reason, Shahrur examines the meaning of freedom from the perspective of a Muslim in the Qur'an and a modern scholar with a more moderate understanding. Because freedom is the most important essence for human beings to live their lives, as well as the greatest gift that Allah has given to human beings. Therefore, everything that contradicts or can even deprive human beings of their rights to freedom must be rejected, so that human beings can live their lives in full freedom.